The Amityville horror - Douglas, Andrew; Bay, Michael; Sony Pictures Home Entertainment (Firm).; Metro-Goldwin-Mayer.; D'Corcorde Recording Corporation (Culver City, Calif. Sony Pictures Home Entertainment; distributed in the Philippines by D'Corcorde Recording Corporation, 2005)
A horror film about a young couple and their children who move into a house that was once the site of a horrific series of murders. Over the next 28 days, they find that the house might be haunted by a murderous presence.
Based on the true story
Based upon a screenplay by Sandor Stern
Director of photography, Peter Lyons Collister ; editors, Christian Wagner, Roger Barton ; music, Steve Jablonsky ; costume designer, David Robinson ; production designer, Jennifer Williams.
Ryan Reynolds, Melissa George, Jesse James, Jimmy Bennett, Chloë Grace Moretz, Rachel Nichols, Philip Baker Hall.
MPAA rating: R; violence, disturbing images, language, brief sexuality, drug use.
VCD.
Keywords: Haunted houses -- Drama; Demonology -- Drama; Parapsychology -- New York (State) -- Amityville -- Drama